Ender's game and philosophy : the logic gate is down - Decker, Kevin S. (Malden, MA : Wiley Blackwell, 2013)
A threat to humanity portending the end of our species lurks in the cold recesses of space. Our only hope is an eleven-year-old boy. Celebrating the long-awaited release of the movie adaptation of Orson Scott Card's novel about highly trained child geniuses fighting a race of invading aliens, this collection of original essays probes key philosophical questions raised in the narrative, including the ethics of child soldiers, politics on the internet, and the morality of war and genocide. Original essays dissect the diverse philosophical questions raised in Card's best-selling sci-fi classic, winner of the Nebula and Hugo Awards and which has been translated in 29 languages.
pt. 1. Third : the making of an impossible child -- pt. 2. Game : cooperation or confrontation? -- pt. 3. Hive-queen : all together now -- pt. 4. War : kill or be killed -- pt. 5. Hegemon : the terrible things are only about to begin.
Includes bibliographical references and index.
Print version record.
Keywords: Card, Orson Scott; Wiggin, Ender -- (Fictitious character); Card, Orson Scott; Wiggin, Ender -- (Fictitious character); Ender's game (Card, Orson Scott); Science fiction, American -- History and criticism; Philosophy in literature; LITERARY CRITICISM -- American -- General; Philosophy in literature; Science fiction, American; Electronic books; Criticism, interpretation, etc